Phenotype analysis and clinical management in a large family with a novel truncating mutation in RASGRP2, the CalDAG‐GEFI encoding gene. Issue 1 (20th June 2017) - Desai, Amrita; Bergmeier, Wolfgang; Canault, Mathias; Alessi, Marie‐Christine; Paul, David S.; Nurden, Paquita; Pillois, Xavier; Jy, Wenche; Ahn, Yeon S.; Nurden, Alan T.
Abstract: Essentials Mutations in the RASGRP2 gene represent a new inherited platelet function disorder. Report a five generation family with a novel frameshift mutation in RASGRP2 (p.F497Sfs*22). Partial platelet activation defect and serious bleeding complications in homozygous patients. Patients respond to recombinant Factor VIIa infusion but not platelet transfusions. Background: Genetic variants in the RASGRP2 gene encoding calcium and diacylglycerol‐regulated guanine nucleotide exchange factor I (CalDAG‐GEFI) represent a new inherited bleeding disorder linked to major defects of platelet aggregation and activation of αIIbβ3 integrin. They are of major interest as CalDAG‐GEFI is receiving attention as a potential target for antiplatelet therapy for prevention and treatment of cardiovascular disorders including arterial thrombosis and atherosclerosis. Objectives: To better understand the phenotypical and clinical profiles of patients with CalDAG‐GEFI deficiency. Patients: We report a five‐generation family with a novel truncating CalDAG‐GEFI mutation detailing clinical management and phenotypic variability. Results: Patients IV.6 & IV.4 manifested with episodes of serious mucocutanous bleeding or bleeding after surgery not responding to platelet transfusion but responding well to recombinant Factor VIIa infusions. Their blood counts and coagulation parameters were normal but platelet aggregation to ADP and collagen was defective. Further work‐up confirmed normal levels of αIIb and β3 in their platelets but decreased αIIbβ3 function. DNA analysis by whole exome sequencing within the BRIDGE‐BPD consortium (Cambridge, UK), allowed us to highlight a homozygous c.1490delT predicted to give rise to a p.F497Sfs*22 truncating mutation near to the C‐terminal domain of CalDAG‐GEFI. Sanger sequencing confirmed that both patients were homozygous for the c.1490delT and 3 out of 4 close family members were heterozygous. Conclusions: A long‐term prospective study is warranted for full clinical exploration of CalDAG‐GEFI to understand the bleeding phenotyes and their management.